Seroprevalence of antibodies against bovine viral diarrhoea virus in cattle under an extensive production system in three districts of Ayacucho, Peru - Arbulú-García, Catherine (2021)
The present study aimed to determine the seroprevalence of antibodies against bovine viral diarrhoea virus (BVDV) in the districts of Chumpi, Coracora and Pullo, Ayacucho region, in March 2018. In total, 460 blood samples were collected from cattle from both sexes and older than four months of age, from rural communities under extensive breeding system. The serum samples were analysed using a commercial indirect ELISA kit. The results showed that 82.56 ± 3.44% (367/460) of the animals presented antibodies against BVDV, with the greatest corrected prevalence in Pullo (89.74 ± 2.75%; 83/96). The high corrected prevalence reported shows a wide distribution of the disease.